A survey of shape variation in keratinized labial teeth of anuran larvae as related to phylogeny and ecology - Vera Candioti, María Florencia (2010)
Labial teeth of anuran tadpoles are keratinized structures derived from the activity of a single epidermal cell of the oral labia; they are not homologous with adult anuran teeth, nor with teeth of other vertebrates. The present study comprises a first approach for studying labial tooth shape variation that will be useful for future studies of comparative development and the functional mechanics of feeding structures. We examined interspecific shape variations in the labial teeth of anuran tadpoles and searched for correlations of these variations with ecomorphological guilds and phylogeny. Species ordination shows that important variations at various taxonomic levels are related mainly to the general curvature of the tooth axis, the angle between the labial tooth base and tip, head length and curvature, and sheath width. The teeth of most basal taxa are broad-based and curved, although some broad-based teeth also characterize some phthanobatrachian species. Teeth of hyloids and ranoids differ in the oral angle, overall curvature, and sheath width. A phylogenetically independent ecomorphological effect is significant only for lotic suctorial and gastromyzophorous guilds; teeth in these forms have short, thick and curved heads, wide sheaths, and generally acute oral angles. The lack of a significant correlation between labial tooth shape and trophic guilds suggests that labial tooth harvesting ability has a wide latitude that could be particularly functional only under specific circumstances.